Progressive multifocal leukoencephalopathy in HIV with atypical presentation and prognostic outcome causing diagnostic dilemma: a case report - Nadhirah Mesran, Nur; Abdul-Razak, Suraya; Md Yasin, Mazapuspavina; Periyasamy, Petrick; Wan Ahmad Kammal, Wan Syahira Ellani; Abd Halim, Haizlene (Termedia Publishing House, 2024)
Progressive multifocal leukoencephalopathy (PML) is a rare demyelinating disease caused by John Cunningham virus (JCV) that affects immunocompromised individuals, particularly human immunodeficiency virus (HIV)-positive. Classical symptoms of PML alter mental status, causing paralysis and diplopia. Bizarre presentations, such as seizures and personality change, are rare in PML, which may lead to a delay in diagnosis and treatment. A 31-year-old HIV-positive Malay man on antiretroviral therapy (ART), presented with two episodes of generalized tonic-clonic seizures. First brain MRI showed a solitary right frontal lobe lesion, for which brain biopsy revealed inflammatory infective process with normal cerebrospinal fluid (CSF) examination, and led to diagnosis of primary lymphoma. Four months later, the patient developed progressive personality changes, reduced cognitive function, and left upper limb paralysis. Second brain MRI showed progression of asymmetrical distribution of white matter changes involving sub-cortical, deep, and periventricular area, a classical feature of PML. ART and intensive neuro-rehabilitation were continued, and the patient s condition slowly improved; however, cognitive function remained affected. Our case is the first reported case of PML with HIV, who survived six years after diagnosis despite initial diagnostic dilemma and poor prognostic factors. This case illustrates that survival is possible with compliance with ART and intensive rehabilitation.